Theoretical Study on Interactions Between Berberine as an Anticancer Drug and DNA - Parchehbaf Jadid, A.; Zarefatin, Leila; Javadi, Leila (Asian Journal of Chemistry, 2012)
In this study, we present the work on the physicochemical interaction between the anticancer alkaloid berberine (BRB) and DNA with the purpose of designing drugs that interact more with DNA. Molecular modeling on the complex formed between berberine and DNA presented that this complex was undeniably fully able of participating in the formation of a stable intercalation site. Besides, the molecular geometries of berberine and the DNA bases (adenine, guanine, cytosine and thymine) were optimized with the aid of the B3LYP/6-31G method. This intercalator has a large polarizability and is a good electron acceptor, while base pairs are good electron donors. B3LYP/6-31G stabilization energies of intercalator… DNA base pair complexes are large (-7.65 kcal/mol for AT···BRB and -3.58 kcal/mol for GC···BRB). It was eventually concluded that the dispersion energy and the electrostatic interaction influenced the stability of the intercalator···DNA base pair complexes. The results exhibited that the berberine changes affected the DNA structure with reference to the bond length, the bond angle, the torsion angle and the charges.